Education and progress in Kant’s pedagogical reflection - Beade, Ileana Paola (Revista Complutense de Educación, 2016)
Kant regards education as a complex process which covers different aspects, such as discipline, instruction and Bildung (formation) – a process whose main goal consists in developing natural dispositions, such as rationality and morality. Bildung, understood mainly as moral and civic education, is considered as the final goal of the educative process: neither discipline nor instruction are enough to achieve the main goal of that process, to wit: the transformation of social institutions. Although discipline and instruction allow human beings to develop the capacities which are necessary to achieve their goals, only Bildung provides the opportunity to achieve, not pragmatic, but moral goals, those which define the intrinsic value of mankind. This paper attempts to explain the ethical premises that support Kant’s conception of educational moral goals. We shall see that Kant’s pedagogy is supported by his conception of human beings as perfectible beings, as well as by the idea of a progressive advancement of mankind. We shall also emphasize the relevance of Kant’s pedagogical principles and his cosmopolitan project in the present context, which is becoming increasingly tangled by ethnic, political and religious conflicts.